(untitled) (Business Vision, 2025)
The way in which political institutions are standardized within a State, and their influence on historical development, is the result of events that can generate paradigmatic changes. Based on this assertion, the research pursued the objective of analyzing the path dependence in national educational policy since the Liberal Revolution in Ecuador in 1895, focusing on secularism as an institution. The theory of public policy changes was used together with the theory of path dependence, which offers analytical inputs to reflect on the standardization and resistance of secularism over time. Together with the use of a qualitative approach and the systematic process tracing as a tool to reconstruct historical information, it is concluded that secularism is resistant but not impenetrable, which supposes traumas in sectoral policy to defend it, evidencing contrary expressions to dismiss it.